2016
DOI: 10.1021/acs.jpcc.5b10233
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling the Native Conduction of Trichalcogenides and Its Ideal Band Alignment for New Photovoltaic Interfaces

Abstract: The trichalcogenides Sb 2 S 3 , Sb 2 Se 3 , Bi 2 S 3 , and Bi 2 Se 3 share an orthorhombic crystal structure and have recently been pointed out as promising materials for application in solar energy harvesting, such as photovoltaic solar cells, because of their ultimate structural and electronic/optical properties. In this work, using a firstprinciples theoretical approach, we investigated the origin of the electrical conduction in bulk systems as well as the energy band alignment in different heterostructures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
60
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(63 citation statements)
references
References 66 publications
3
60
0
Order By: Relevance
“…Therefore, we tentatively attributed H1 and H2 defects to V Sb and Se Sb defects, respectively. As reported by Tumelero et al 44 , the antisite defects dominated the distribution of defects in trichalcogenides due to the similar sizes of the constituent atoms. Our previous simulation also showed that Se Sb and antimony antisite (Sb Se ) are acceptor and donor defects, respectively 11 .…”
Section: Resultssupporting
confidence: 62%
“…Therefore, we tentatively attributed H1 and H2 defects to V Sb and Se Sb defects, respectively. As reported by Tumelero et al 44 , the antisite defects dominated the distribution of defects in trichalcogenides due to the similar sizes of the constituent atoms. Our previous simulation also showed that Se Sb and antimony antisite (Sb Se ) are acceptor and donor defects, respectively 11 .…”
Section: Resultssupporting
confidence: 62%
“…1, the literature in thermoelectric materials often shows qualitatively different results. [14][15][16][17][18] Here, we consider PbTe a well studied material with strong spin-orbit coupling, to demonstrate the challenges posed in first-principles based density functional theory (DFT) calculations aimed at bulk properties, [19][20][21][22][23][24][25] and intrinsic defects. 14,15,[26][27][28] The DFT calculations employing the local density approximation (LDA) 29 or the generalized gradient approximation (GGA) 30 for exchange correlation provide only a qualitative description of the electronic structure of PbTe.…”
Section: Introductionmentioning
confidence: 99%
“…The mobility of Sb 2 Se 3 along the [0 0 1] direction can be as high as 20 cm 2 V −1 s −1 , and the electron diffusion length along the [0 0 1] direction under high illumination is 1.7 µm . First‐principles theoretical calculations demonstrated that the electrical properties of antimony chalcogenides were ruled by native point defects (mainly antisites) and that these materials could lead to high‐efficiency solar cells because of their ultimate structural and electronic/optical properties . Typical properties of antimony chalcogenides are summarized in Table .…”
Section: Basic Properties Of Antimony Chalcogenide Materialsmentioning
confidence: 99%